2014
DOI: 10.1002/anie.201308899
|View full text |Cite
|
Sign up to set email alerts
|

The Prodrug Platin‐A: Simultaneous Release of Cisplatin and Aspirin

Abstract: Cancer-associated inflammation induces tumor progression to the metastatic stage, thus indicating that a chemo-anti-inflammatory strategy is of interest for the management of aggressive cancers. The platinum(IV) prodrug Platin-A was designed to release cisplatin and aspirin to ameliorate the nephrotoxicity and ototoxicity caused by cisplatin. Platin-A exhibited anticancer and anti-inflammatory properties which are better than a combination of cisplatin and aspirin. These findings highlight the advantages of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
173
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(174 citation statements)
references
References 30 publications
1
173
0
Order By: Relevance
“…[12][13][14][15] Therefore, much effort has been made to overcome the side effects and improve the antitumor activity of platinum-based drugs. [16][17][18][19] Oxaliplatin, one of the best sale anticancer drugs, has become the standard first line therapy in case of metastatic colorectal cancer, which can exhibit activity against cisplatin and carboplatin resistant cancers. 20 It is noted that oxaliplatin possesses a cycloalkyl framework, 1R,2R-diaminocyclohexane (abbreviated as 1R,2R-DACH), which acts as a carrier ligand providing steric hindrance when interacting with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Therefore, much effort has been made to overcome the side effects and improve the antitumor activity of platinum-based drugs. [16][17][18][19] Oxaliplatin, one of the best sale anticancer drugs, has become the standard first line therapy in case of metastatic colorectal cancer, which can exhibit activity against cisplatin and carboplatin resistant cancers. 20 It is noted that oxaliplatin possesses a cycloalkyl framework, 1R,2R-diaminocyclohexane (abbreviated as 1R,2R-DACH), which acts as a carrier ligand providing steric hindrance when interacting with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Many studies have reported on dual therapies that treat both inflammation and cancer,b ut few studies have focused directly on inflammation caused by PTT. [7] Among av ast array of nanomaterials,A uNRs offer ease of preparation, ready multi-functionalization and efficient conversion of NIR optical energy into heat. [8] Nevertheless,it is necessary to improve the thermostability of AuNRs in order to extend their biomedical applications during prolonged laser irradiation.…”
mentioning
confidence: 99%
“…However, the human pharmacokinetic studies revealed that from 25 to 45 % of intravenously injected cisplatin is excreted in the urine, while the rest is distributed throughout the body [39,40]. Hence, small quantities, in the order of ppb ( μ g/l) or possibly ppt (0.001 ng/l) are able to reach tumoral cells [41][42][43].…”
Section: Survey Of Results and Discussionmentioning
confidence: 99%